2005
DOI: 10.1177/002215540505300102
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Effects of Formalin Fixation with Citraconic Anhydride and Heat: A Universal Antigen Retrieval Method

Abstract: Formalin is a commonly used fixative for tissue preservation in pathology laboratories. A major adverse effect of this fixative is the concealing of tissue antigens by protein cross-linking. To achieve a universal antigen retrieval method for immunohistochemistry under a constant condition, we developed a new method in which the effects of formalin fixation were reversed with citraconic anhydride (a reversible protein cross-linking agent) plus heating. Formalin-fixed, paraffin-embedded tissues from various org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 24 publications
2
97
0
Order By: Relevance
“…Recently, there is increasing evidence that formalin-induced macromolecule crosslinking can be reversed under high temperature. [29][30][31] Heating treatment not only transformed intermolecular cross-linked polymers into monomers 24,29,30 but also partially restored enzymatic reactivity of formalinfixed RNase A. 31 Based on literature and our observations, we believe that heating effect, either direct heating as described herein or microwave/ ultrasound-induced heating, plays a pivotal role in the NDME procedures for FFPE tissues.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, there is increasing evidence that formalin-induced macromolecule crosslinking can be reversed under high temperature. [29][30][31] Heating treatment not only transformed intermolecular cross-linked polymers into monomers 24,29,30 but also partially restored enzymatic reactivity of formalinfixed RNase A. 31 Based on literature and our observations, we believe that heating effect, either direct heating as described herein or microwave/ ultrasound-induced heating, plays a pivotal role in the NDME procedures for FFPE tissues.…”
Section: Discussionsupporting
confidence: 52%
“…Primary antibodies used were: anti-Folr1 (custom-made by GenScript; 1:400), anti-C-cadherin (6B6, Developmental Studies Hybridoma Bank; 1:50), anti-β-tubulin (E7, Developmental Studies Hybridoma Bank; 1:300), anti-E-cadherin (5D3, Developmental Studies Hybridoma Bank; 1:100), anti-GFP (GFP-1020, Aves Labs; 1:500), anti-Sox2 (AF2018, R&D Systems; 1:300), anti-m-Cherry (ab 167453, Abcam; 1:500). Antigen retrieval was performed by microwaving samples in 0.05% citraconic anhydride, pH 7.4 (Namimatsu et al, 2005). Briefly, a rack with slides was placed in a 200 ml glass container covered with plastic wrap, boiled for 15 s at maximum power (1200 W) followed by 3 min wait in hot buffer.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Solutions of 6 M guanidine HCL with BME 12 and aqueous 0.05% citraconic anhydride 13 were also evaluated. The surrogates were then homogenized with a disposable pellet pestle (Kontes Scientific, Vineland, NJ, USA), followed by two 10-s cycles of sonication on ice using a Sonic Dismembrator, model 550, fitted with a 0.125-inch tapered microtip (Fisher Scientific).…”
Section: Solubilization and Recoverymentioning
confidence: 99%
“…These results are shown in Table 4. Namimatsu et al 13 reported improved immunohistochemical staining of Tissue surrogates heated in 6 M guanidine HCl supplemented with 0.5 M BME, a disulfide-reducing agent, resulted in a protein recovery of 58%. Recovery efficiency was increased to 470% in solutions of 20 mM Tris HCl with 2% SDS and 0.5 M BME (Table 4).…”
Section: Effects Of Other Buffer Formulations On Recovery Efficiencymentioning
confidence: 99%